CODE MIXING IN RADITYA DIKA’S MANUSIA SETENGAH SALMON AND KAMBING JANTAN NOVELS - Dian Sri Utami; Iskandar Zulkarnain; Linda Astuti Rangkuti (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This study dealt with the use of code mixing in Raditiya Dika’s Manusia Setengah Salmon and Kambing Jantan novels. This study was conducted by applying descriptive qualitative design. The data of this study were collected from two novels by Raditiya Dika: Manusia Setengah Salmon and Kambing Jantan novels. The study’s findings showed that there were only two types of code mixing used in both novels of Manusia Setengah Salmon and Kambing Jantan. They were insertion and alternation types. In Manusia Setengah Salmon novel, insertion type was 95% and alternation type was 5%. While in Kambing Jantan novel, insertion type was 65% and alternation type was 35%. Thus, it can be concluded that insertion type was the dominant type of code mixing used in Manusia Setengah Salmon and in Kambing Jantan novel.